Skrining dan Edukasi Pencegahan Stroke dan Penyakit Jantung di Desa Lalimbue oleh AMSA-UHO (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Cardiovascular diseases are the leading cause of death worldwide, accounting for 17.9 million deaths annually. Stroke and heart attacks often go undetected due to their silent nature. This community service activity aimed to increase community knowledge about stroke and heart attacks and conduct early detection through health screening. The activity was conducted in Lalimbue Village, Kapoiala District, Konawe Regency on May 11 and 18, 2025. Methods included healthy exercise, educational talk show, first aid workshop, and health screening (blood pressure, blood glucose, cholesterol). Knowledge evaluation used pre-test and post-test with 10 questions. Results showed 56 participants on implementation day and 17 on follow-up. Pre-test showed 23% had good knowledge, 34% moderate, and 43% poor. Post-test showed 87% good knowledge and 13% moderate. Health screening found 10.7% with hypertension and 10.7% with diabetes mellitus on implementation day. Follow-up found 47.1% with hypertension and 23.5% with diabetes mellitus. This study concluded that health education is effective in increasing community knowledge about stroke and heart attack prevention, and health screening is important for early detection of cardiovascular and metabolic diseases.